2014
DOI: 10.1111/joor.12163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oro‐facial function in young subjects with temporomandibular disorders

Abstract: The aim of this study was to evaluate bite force (BF) and oro-facial functions at different dentition phases (initial-mixed, intermediate-mixed, final-mixed and permanent dentition) in children and adolescents diagnosed with temporomandibular disorders (TMDs). The sample was selected from four public schools in Piracicaba, São Paulo, Brazil. Of the 289 participants recruited, aged 8-14 years old, 46 were placed into the TMD group. TMD was diagnosed using Axis I of the Research Diagnostic Criteria for Temporoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
(67 reference statements)
3
13
1
5
Order By: Relevance
“…12 Other authors found percentages of TMD symptoms and signs between 10% and 25% among the children in their studies. 48,26,32 These percentages were closer to the percentages found in this study. This range of prevalence data raises the question whether children’s age might be an explanatory factor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…12 Other authors found percentages of TMD symptoms and signs between 10% and 25% among the children in their studies. 48,26,32 These percentages were closer to the percentages found in this study. This range of prevalence data raises the question whether children’s age might be an explanatory factor.…”
Section: Discussionsupporting
confidence: 89%
“…While some authors found that girls were more likely than boys to experience TMD 4,5,8,1925 , other studies found no gender differences 2631 or were inconclusive Kobayashi. 32 It is therefore worthwhile to further explore the question whether girls and boys differ in the frequencies with which they report TMD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Como é importante usar critérios diagnósticos apropriados de DTM, são necessários instrumentos precisos para avaliar as funções relacionadas ao sistema estomatognático (Kobayashi et al, 2014). Bakke et al(2007) desenvolveram e testaram o The Nordic Orofacial Test-Screening -NOT-S, um instrumento para a triagem da disfunção orofacial por meio de uma entrevista estruturada e exame clínico, com escala dicotômica.…”
Section: Revisão De Literaturaunclassified
“…A maioria dos pacientes com sintomas de DTM têm entre 20 e 50 anos de idade (Murphy et al, 2013), no entanto, pode ocorrer também em crianças e adolescentes (Tecco et al, 2011;Kobayashi et al, 2014). Aproximadamente 5 a 9% da população adulta apresenta sintomas significantes de DTM (Plesh et al, 2011;Al-Saleh et al, 2012) com maior prevalência em mulheres (Dao e LeReshe, 2000;Gonçalves et al, 2010;Maixner et al, 2011;Schmid-Schwaps et al, 2013).…”
Section: Introductionunclassified
See 1 more Smart Citation